Analysis of the Systematic Subject Matter for Fiqh in Islamic Religious Education Lessons at Schools in the 2022 Prototype Curriculum - Basuki Basuki (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research is motivated by the unsystematic subject matter of fiqh in Islamic Religious Education (PAI) lessons in schools in the 2013 curriculum. The understanding of the subject matter of fiqh must be systematic or sequential. If students learn the subject matter of fiqh not systematically or sequentially, it will impact the confusion of students' mastery. The systematic confusion in discussing the subject matter of fiqh in Islamic Religious Education (PAI) lessons in the 2013 curriculum at the school have been resolved by the government through the 2022 prototype curriculum policy set out in the decision of the Head of the Standards, Curriculum, and Educational Studies Agency, Ministry of Education and Culture. Education, Culture, Research, and Technology of the Republic of Indonesia number 008/H/KR/2022. This research aims to describe and analyze the systematically subject matter of fiqh in Islamic Religious Education (PAI) lessons in schools in the 2022 prototype curriculum. This type of research is library research. With content analysis, researchers found that the systematics of fiqh subject matter in Islamic Religious Education (PAI) lessons in schools in the 2022 prototype curriculum had been arranged hierarchically-systematically.